Implementing Teaching Model Templates for supporting Flipped Classroom-enhanced STEM Education in Moodle - Sergis, S.; Vlachopoulos, P.; Sampson, Demetrios; Pellicione, L. (2016)
Science, Technology, Engineering, and Mathematics (STEM) Education has been associated with the need for cultivating students’ inquiry and problem-solving skills by exploiting appropriate student-centered teaching approaches. At the same time, the Flipped Classroom (FC) model has been proposed as a blended learning means to enhance such teaching approaches by effectively reallocating their learning activity distribution towards maximizing student engagement and scaffolding by the teachers. In order to reap the benefits of FC-enhanced teaching approaches when designing and delivering their STEM learning interventions, however, teachers (especially novices) could benefit from having access to “generic” teaching model templates that they can adjust in their specific needs. In this context, we have introduced a set of FC-enhanced teaching model templates focusing on two widely used STEM-appropriate teaching models, i.e., the Inquiry- and Problem-based teaching models. Capitalizing on this, the contribution of this chapter is the presentation of the implementations of the aforementioned teaching templates in Moodle, a widely used open source Learning Management System. The anticipated added value of the proposed adaptable Moodle templates is to provide support to (novice) STEM teachers, not only in their educational design (through the use of the proposed FC-enhanced teaching model templates), but also in the delivery of their lessons and/or educational scenarios.